Advanced force coordination of lower extremities during visuomotor control task in soccer players - Lee, T. L.; Ko, D. K.; Kang, N. (Research Quarterly for Exercise and Sport, 2023)
Purpose This study is aimed to determine specific bilateral lower extremity motor performances and coordination patterns in soccer players with healthy controls using the bilateral force control paradigm. We hypothesized that soccer players would show more advanced bilateral force control performances than untrained controls.